From Seismic Quiescence to Surged Activity After Decades of Wastewater Disposal: A Case Study in Central‐West Alberta, Canada. Issue 22 (10th November 2021) - Yu, Hongyu; Kao, Honn; Visser, Ryan; Wang, Bei
Abstract: Injection‐induced earthquakes associated with wastewater disposal (WD) in the Western Canadian Sedimentary Basin are much fewer than those linked to hydraulic fracturing. Recently, 43 WD‐related earthquakes (M1.3–3.9) occurred in a historically seismically quiet area where long‐term injections became intensive since 2018, foreshadowing a critical stress state accumulated from long‐term injections. Our improved earthquake locations show that the injection well targeting the deeper middle‐upper Devonian aquifer system causes more vigorous seismicity with a wide range of stress drop values (0.8–230 MPa) compared to other shallower wells. Three physical mechanisms may collectively lead to the observed seismic pattern: (a) the underlying Devonian reef system makes it easier for injected fluids to migrate horizontally, (b) fluids can be channeled into the widespread critical faults and migrate vertically to cause earthquakes along it, and (c) aseismic slip probably triggered within the Duvernay formation by fluid migrating can further facilitate seismicity at shallower depths. Plain Language Summary: Earthquakes can be triggered during the injections of both hydraulic fracturing and wastewater disposal. In the Western Canadian Sedimentary Basin, the latter injection type appears to have caused much fewer earthquakes than the former. Recently, a sequence of 43 small‐to‐moderate‐sized earthquakes occurred in a seismically quiet area, where injections have been safely operated for more than two decades prior to becoming intensive in 2018. The refined earthquake distribution confirms that these earthquakes are related to disposal injections. The inception of local seismicity implies that long‐term injections probably have loaded nearby fault structures to rupture. Among the four active wells, the one with a deeper injection depth caused more earthquakes than other shallower wells. As the injection of the deeper well is close to the ancient reef system, horizontal fluid migration is facilitated and more likely to reach nearby faults. Fluid migration along subvertical faults can cause deeper earthquakes in the basement and aseismic creep in the overlying shale formation. The induced aseismic slip can further load the adjacent fault segment and foster earthquakes at shallow depths. The fact that stress released by individual earthquakes varies widely between 0.8 and 230 MPa also hints the existence of aseismic creep. Key Points: Emerging seismicity in a historically seismically quiet area in western Canada is linked to the intensive wastewater disposal injections Injection targeting the deeper upper‐middle Devonian aquifer has caused more vigorous seismicity with varying stress drop values Fluid migration facilitated by the Devonian reef system and aseismic slip in the Duvernay are proposed to boost the seismic triggering